Sirtuin 6 Protects Against Oxidative Stress and Vascular Dysfunction in Mice - Greiten, Lawrence E.; Zhang, Bin; Roos, Carolyn M.; Hagler, Michael; Jahns, Fritz-Patrick; Miller, Jordan D. (Frontiers in Physiology, 2021)
Objective Sirtuin deacetylases are major regulators of organismal aging, and while depletion of Sirtuin 6 (SIRT6) in mice results in a profound progeroid phenotype, the role of SIRT6 in the regulation of vasomotor function is unknown. Thus, our objective was to test the hypothesis that reductions in SIRT6 elicit endothelial dysfunction in young, genetically altered mice. Results and Approach We used young (3 month old), littermate-matched, SIRT6 wild-type (WT) and SIRT6 heterozygous (HET) mice. SIRT6 expression (qRT-PCR) was reduced by 50% in HET mice. Carotid vessel responses to acetylcholine, sodium nitroprusside, U46619, and serotonin were examined in isolated organ chamber baths. Relaxation in response to acetylcholine (ACH) was impaired in HET mice compared to littermate-matched WT controls (67  3% versus 76%  3% respectively; p < 0.05), while responses to sodium nitroprusside were unchanged. Short-term incubation of carotid rings with the NAD(P)H oxidase inhibitor, apocynin, significantly improved in vessels from HET mice but not their WT littermates. Peak tension generated in response to either U46619 or serotonin was significantly blunted in HET mice compared to their WT littermates. Conclusions These data suggest that SIRT6 is a key regulator of vasomotor function in conduit vessels. More specifically, we propose that SIRT6 serves as a tonic suppressor of NAD(P)H oxidase expression and activation, as inhibition of NAD(P)H oxidase improved endothelial function in SIRT6 haploinsufficient mice. Collectively, SIRT6 activation and/or histone acetyltransferase inhibition may be useful therapeutic approaches to reduce endothelial dysfunction and combat age-associated cardiovascular disease.